The effect of self-employment on income inequality - Stefan Schneck (Institut für Mittelstandsforschung (IfM) Bonn, 2018)
It is well known that the self-employed are over-represented at the bottom as well as the top of the income distribution. This paper shifts the focus from the income situation of the self-employed to the distributive effects of a change in self-employment rates. With representative German data and unconditional quantile regression analysis we show that an increase in the proportion of self-employed individuals in the labor force increases income polarization by tearing down oors at the bottom and allowing higher earnings potentials at the very top of the hourly income distribution. Recentered in uence function regression of inequality measures corroborate that self-employment is a source of income inequality in the labor market.
Keywords: L26; D31; 330; income; earnings inequality; self-employment